States in the global economy : bringing domestic institutions back in - Weiss, Linda (Linda M.) (Cambridge studies in international relations, 2003)
General opinion holds that globalisation limits the state's capacity for domestic government. This book questions the thesis that the state's role has been restricted. The contributors argue that globalisation can enable as well as constrain, and that its effects depend on the character of a country's domestic institutions.